Entombed - Fairstein, Linda A. (Fairstein, Linda A. Alexandra Cooper novels., 2005)
Workers demolishing a nineteenth-century brownstone where Edgar Allan Poe once lived discover a human skeleton entombed -- standing -- behind a brick wall. When sex crimes prosecutor Alexandra Cooper hears about the case, it strikes her as a classic Poe scene...except that forensic evidence shows that this young woman died within the last twenty-five years. Meanwhile, Alex's old nemesis the Silk Stocking Rapist is once again terrorizing Manhattan's Upper East Side. The attacks soon escalate to murder, and the search leads Alex and detectives Mercer Wallace and Mike Chapman to the city's stunning Bronx Botanical Gardens. There, an enigmatic librarian presides over the Raven Society, a group devoted to the work of Poe. In exploring the fabled writer's tormented life for clues, Alex will cross paths with a cunning killer and face some of the greatest challenges of her career. Entombed is masterful, exhilarating crime fiction from one of crime writing's most dazzling stars.